Ferroptosis due to Cystathionine γ Lyase/Hydrogen Sulfide Downregulation Under High Hydrostatic Pressure Exacerbates VSMC Dysfunction - Jin, Ruxi; Yang, Ruixue; Cui, Changting; Zhang, Haizeng; Cai, Jun; Geng, Bin; Chen, Zhenzhen (Frontiers in Cell and Developmental Biology, 2022)
Hydrostatic pressure, stretch and shear are major biomechanical forces of vessels and play critical role in genesis and development of hypertension. Our previous work demonstrated that high hydrostatic pressure (HHP) promoted vascular smooth muscle cells (VSMCs) two novel subsets: inflammatory and endothelial-function inhibitory VSMCs, then exacerbated VSMCs dysfunction. However, the underlying mechanism remains unknown. Here, we firstly identified that aortic GPX4 (a core regulator of ferroptosis) significantly downregulated association with VSMC novel phenotypes elevation in SHR rats and hypertension patients. In primary VSMCs, HHP (200 mmHg) increased iron accumulation, ROS production and lipid peroxidation compared with normal pressure (100 mmHg). Consistently, ferroptosis related gene (COX-2, TFRC, ACSL4 and Nox-1) expression was also upregulated. Ferroptosis inhibitor ferrostatin-1 (Fer-1) administration blocked HHP-induced VSMC inflammatory (CXCL2 expression) and endothelial-function inhibitory (AKR1C2 expression) phenotyping switch association with elevation GPX4 expression, reduction reactive oxygen species (ROS) and lipid peroxidation production. In contrast, ferroptosis inducer RLS3 heightened HHP-induced CXCL2 and AKR1C2 expression. These data indicate HHP triggering ferroptosis contributes to VSMC inflammatory and endothelial-function inhibitory phenotyping switch. In mechanism, HHP reduced VSMC GSH content and cystathionine gamma-lyase (CSE)/hydrogen sulfide (H2S)-an essential system for GSH generation. Supplementation H2S donor-NaHS heightened the VSMC GSH level, alleviated iron deposit, ROS and lipid peroxidation production, and vice versa. NaHS administration rescue both HHP- and RLS3-induced ferroptosis. Collectively, HHP down-regulated VSMC CSE/H2S triggering GSH level reduction, resulting in ferroptosis, and which contributed to the genesis of VSMC inflammation and endothelial function inhibitory phenotypes.